Where the creek bends [large type] - Miller, Linda Lael (Thorndike Press large print dynamic drama., 2025)
"Madison Bettencourt has moved back home to Montana to care for her grandmother. As Madison rattles around her family home, childhood memories come flooding back. Bliss Morgan transformed eight-year-old Madison with her loyalty, and for a while, the two girls were as close as can be. But Madison never understood why Bliss suddenly vanished. Before she can begin again, Madison must uncover what happened to Bliss, and Liam McKettrick--a widowed dad trying to repair his relationship with his children--becomes her unlikely ally. Yet there are mysteries that Madison hesitates to explore with anyone, and strange energies in Bettencourt Hall that blur the lines between past and present"--